Living apart together: The economic value of ethnic diversity in cities. (October 2022) - Bakens, Jessie; Florax, Raymond JGM; de Groot, Henri LF; Mulder, Peter
In consumer cities, the presence and location of immigrants impacts house prices through two channels, which both can be valued positively as well as negatively: (i) their presence and contribution to population diversity and (ii) the creation of immigrant-induced consumer amenities like those associated with ethnic restaurants in terms of both their quantity as well as diversity. We hypothesize that these two mechanisms create a trade-off in which city dwellers want to live apart yet consume together. We use unique microdata of house prices and ethnic restaurants in the city of Amsterdam over the 1996–2011 period and a generalized propensity score (GPS) matching technique for multiple continuous treatments to estimate the trade-off between consumers' love for ethnic goods and their variety on the one hand, and ethnic residential composition on the other hand. We find evidence for the existence of such a trade-off: proximity to ethnically diverse restaurants indeed compensates for a negative correlation between the presence of immigrants and house prices. This trade-off mostly holds for neighborhoods featuring both a diverse population and a high level of amenities in terms of restaurants.